The eye of the elephant eaudiobook An epic adventure in the african wilderness. - Owens, Mark (Tantor Media, 2019)
The authors of Secrets of the Sahara battle the elephant poachers of Zambia in this "exciting . . . part adventure story, part wildlife tale" ( The Boston Globe ). Intelligent, majestic, and loyal, with lifespans matching our own, elephants are among the greatest of the wonders gracing the African wilds. Yet, in the 1970s and 1980s, about a thousand of these captivating creatures were slaughtered in Zambia each year, killed for their valuable ivory tusks. When biologists Mark and Delia Owens, residing in Africa to study lions, found themselves in the middle of a poaching fray, they took the only side they morally could: that of the elephants. The Eye of the Elephant recounts the Owens's struggle to save these innocent animals from decimation, a journey not only to supply the natives with ways of supporting their villages, but also to cultivate support around the globe for the protection of elephants. Filled with daring exploits among disgruntled hunters, arduous labor on the African plains, and vivid depictions of various wildlife, this remarkable tale is at once an adventure story, a travelogue, a preservationist call to action, and a fascinating examination of both human and animal nature.